Evolution of Prospective Secondary Education Economics Teachers’ Personal and Emotional Metaphors - Mellado, Lucía; Parte, Laura; Sánchez-Herrera, Susana; Bermejo, María Luisa (Frontiers in Psychology, 2021)
This paper examines personal and emotional metaphors of prospective economics teachers about the roles they themselves as teachers and their pupils would play by analysing their drawings and responses to open questions. To analyse the evolution of future instructors, the paper provides a longitudinal study using two periods: before and after their teaching practicum. Metaphors are classified into four categories: behaviourist/transmissive, cognitivist/constructivist, situative/socio-historical, and self-referential. Emotions are classified as primary or social, and positive, negative, or neutral. The results show that teacher metaphors changed from teacher-centred to pupil-centred models considering the period before and after the practicum. The most common pupil metaphors are behaviourist and cognitivist, increasing after the practicum. Finally, most of the emotions expressed are positive and social, increasing also after the practicum